1998
DOI: 10.1017/s0952523898156122
|View full text |Cite
|
Sign up to set email alerts
|

Non-monotonic contrast behavior in directionally selective ganglion cells and evidence for its dependence on their GABAergic input

Abstract: We serendipitously discovered that the preferred-direction responses of ON-OFF directionally selective (DS) ganglion cells in the rabbit retina fall as a function of contrast when the contrast of a moving bar exceeds about 100%. Null-direction responses did not fall for contrasts up to 400%. Because the non-monotonic (rise-then-fall) behavior as a function of contrast occurred only for preferred-direction responses, it must depend on the mechanism of directional selectivity. It became thus of interest to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 28 publications
1
12
2
Order By: Relevance
“…We note that, contrary to the results reported by Merwine et al (1998) for contrast, we did not observe a fall in response magnitude at high luminance levels. This, however, may be explained by the possibility that the luminance levels that we tested were not high enough to elicit this effect.…”
Section: Luminance Vs Contrastcontrasting
confidence: 86%
See 3 more Smart Citations
“…We note that, contrary to the results reported by Merwine et al (1998) for contrast, we did not observe a fall in response magnitude at high luminance levels. This, however, may be explained by the possibility that the luminance levels that we tested were not high enough to elicit this effect.…”
Section: Luminance Vs Contrastcontrasting
confidence: 86%
“…Generally, as the luminance increased, the mean number of spikes also increased, but in a highly nonlinear fashion: at the low luminance levels it exhibited a rapid rise followed by a plateau indicating saturation at the high luminance levels. Contrary to the results reported by Merwine et al (1998) for contrast, we did not observe a fall in response at high luminance levels, possibly because the luminance levels that we tested were not high enough to elicit this effect. As in the case of speed, we found that the luminance tuning curves were similar in shape independent of direction, although they differed in maximum and minimum values.…”
Section: Luminance Tuning Curvescontrasting
confidence: 86%
See 2 more Smart Citations
“…A hallmark of retinal DS cells is their surprising robustness: They easily outperform their counterparts in the primary visual cortex (V1) in many respects: ON-OFF DS cells detect the direction of motion within their receptive field centre more reliably, largely independent of contrast [56] and velocity [37, 65,88] and even for small movements of a few micrometres [38]. Direction discrimination is roughly constant over a velocity range of more than two orders of magnitude (reviewed in [37]).…”
Section: Ds Retinal Ganglion Cellsmentioning
confidence: 99%